The Effect of Halal Label, P-Irt Label, Price on Purchase Intention and Its Impact to Purchase Decisions in Tuban, Indonesia - Maulidah, Afsah Indah; Wulandari, Kartika; Kristiyoningsih, Kristiyoningsih (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2024)
Micro, Small and Medium Enterprises (MSMEs) are an economic sector that has a significant impact on product sales. Micro, Small and Medium Enterprises (MSMEs) in the Jatirogo subdistrict, Tuban district, are one of the locations where MSMEs have been established which empower them through innovation and the use of local products for consumption. The purpose of this research is to determine the influence of the halal label, P-IRT label and price on purchase intention and its impact on consumer decisions. This research uses the lameshow formula. The sample in this study consisted of 100 respondents. Purchase interest has an impact on purchasing decisions which influence the development of MSMEs in the future, as well as MSMEs currently having to be able to survive in this onslaught with the abundance of modern and unique processed foods. Thus, it is necessary to follow the rules provided by the government, namely halal certification and P-IRT permits. This research analyzed using SEM-PLS method by analyzing the tools used in SMARTPLS. The research results found that price has a positive and significant influence on buying interest; Purchase interest has a positive and significant influence on consumer decisions. The price of MSME products is influenced by purchasing interest on consumer decisions, while the halal label and P-IRT label do not have a significant effect on purchasing interest and purchasing decisions. So that, product prices influence purchasing interest in consumer decisions and purchasing interest has an impact on consumers in making purchasing decisions for MSME products.